Pengaruh Dana Bantuan Operasional Sekolah (Bos) Terhadap Kinerja Keuangan - uliawati, uliawati (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2021)
This study aims to determine the effect of school operational fund (B0S) on financial performance. The data used in this study uses secondary data with quantitative research methods with associative approaches, which are then processed with the help of SPSS 24 using normality tests and test t (partial). And from these results this study shows the school operational assistance funds (BOS) and education support funds influence financial performance. From year 2014- 2018.